Silanediol versus chlorosilanol: hydrolyses and hydrogen-bonding catalyses with fenchole-based silanes - Fox, Falco; Neudörfl, Jörg M.; Goldfuss, Bernd (Beilstein Journal of Organic Chemistry, 2019)
Biphenyl-2,2’-bisfenchyloxydichlorosilane (7, BIFOXSiCl2) is synthesized and employed as precursor for the new silanols biphenyl-2,2’-bisfenchyloxychlorosilanol (8, BIFOXSiCl(OH)) and biphenyl-2,2’-bisfenchyloxysilanediol (9, BIFOXSi(OH)2). BIFOXSiCl2 (7) shows a remarkable stability against hydrolysis, yielding silanediol 9 under enforced conditions. A kinetic study for the hydrolysis of dichlorosilane 7 shows a 263 times slower reaction compared to reference bis-(2,4,6-tri-tert-butylphenoxy)dichlorosilane (14), known for its low hydrolytic reactivity. Computational analyses explain the slow hydrolyses of BIFOXSiCl2 (7) to BIFOXSiCl(OH) (8, Ea = 32.6 kcal mol−1) and BIFOXSiCl(OH) (8) to BIFOXSi(OH)2 (9, Ea = 31.4 kcal mol−1) with high activation barriers, enforced by endo fenchone units. Crystal structure analyses of silanediol 9 with acetone show shorter hydrogen bonds between the Si–OH groups and the oxygen of the bound acetone (OH···O 1.88(3)–2.05(2) Å) than with chlorosilanol 8 (OH···2.16(0) Å). Due to its two hydroxy units, the silanediol 9 shows higher catalytic activity as hydrogen bond donor than chlorosilanol 8, e.g., C–C coupling N-acyl Mannich reaction of silyl ketene acetals 11 with N-acylisoquinolinium ions (up to 85% yield and 12% ee), reaction of 1-chloroisochroman (18) and silyl ketene acetals 11 (up to 85% yield and 5% ee), reaction of chromen-4-one (20) and silyl ketene acetals 11 (up to 98% yield and 4% ee).
Keywords: hydrogen bonds; hydrolysis; ion pairs; organocatalysis; silanediol